2017
DOI: 10.3389/fphar.2017.00209
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Mapping Techniques Show Clozapine Impairs Neurogenic and Myogenic Patterns of Activity in the Colon of the Rabbit in a Dose-Dependent Manner

Abstract: Background: Clozapine, an antipsychotic used in treatment-resistant schizophrenia, has adverse gastrointestinal effects with significant associated morbidity and mortality. However, its effects on defined patterns of colonic contractile activity have not been assessed.Method: We used novel radial and longitudinal spatiotemporal mapping techniques, combined with and monitoring of ambient lumen pressure, in ex vivo preparations of triply and of singly haustrated portions of rabbit colon. We identified the contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…103 It has been demonstrated that clozapine, but not norclozapine, has potent effects on the motility of the colon of a rabbit, thus inhibiting neurogenic contractions at lower concentrations and myogenic contractions at higher concentrations. 104 These effects may be mediated by cholinergic and serotonergic receptors, presumably via M1–M3 and 5HT-3 and 5HT-7 receptors. Moreover, de Alvarenga and colleagues 105 showed that clozapine significantly reduced the frequency of cycles of contractions of zebrafish larvae gastrointestinal tracts through anticholinergic action.…”
Section: Clozapine Mechanism Of Action and Relationships With Adversementioning
confidence: 99%
“…103 It has been demonstrated that clozapine, but not norclozapine, has potent effects on the motility of the colon of a rabbit, thus inhibiting neurogenic contractions at lower concentrations and myogenic contractions at higher concentrations. 104 These effects may be mediated by cholinergic and serotonergic receptors, presumably via M1–M3 and 5HT-3 and 5HT-7 receptors. Moreover, de Alvarenga and colleagues 105 showed that clozapine significantly reduced the frequency of cycles of contractions of zebrafish larvae gastrointestinal tracts through anticholinergic action.…”
Section: Clozapine Mechanism Of Action and Relationships With Adversementioning
confidence: 99%
“…CIGH is defined as an acquired state of delayed transit through the gastrointestinal tract (i.e. transit time >2 standard deviations [SD] above the mean), colloquially known as clozapine-related ‘slow gut’, resulting from the drug’s pharmacological actions on the enteric nervous system [ 7 ]. In vitro, clozapine is shown to have potent effects on the mammalian colon, inhibiting neurogenic and, at higher concentrations, myogenic contractions, profoundly disrupting gastrointestinal motility [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…transit time >2 standard deviations [SD] above the mean), colloquially known as clozapine-related ‘slow gut’, resulting from the drug’s pharmacological actions on the enteric nervous system [ 7 ]. In vitro, clozapine is shown to have potent effects on the mammalian colon, inhibiting neurogenic and, at higher concentrations, myogenic contractions, profoundly disrupting gastrointestinal motility [ 7 ]. These effects can be reversed by carbachol and to some extent by serotonin, suggesting both anticholinergic and anti-serotonergic mechanisms [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common adverse effects of clozapine are sedation, hypersalivation, constipation, hypotension, hypertension, tachycardia, weight gain, fever, seizure, nocturnal enuresis, neutropenia/agranulocytosis, gastroesophageal reflux disease (GERD) [6][7][8][9][10][11][12]. The uncommon or unusual adverse effects are agranulocytosis/neutropenia, colitis, delirium, eosinophilia, heat stroke, hepatic failure, interstitial nephritis, ocular pigmentation, pancreatitis, parotid gland swelling, pericardial effusion, pneumonia, reflux esophagitis, stuttering, vasculitis and thrombocytopenia [6,[13][14][15][16][17]. Serious haematological and cardiovascular adverse effects are agranulocytosis, thromboembolism, cardiomyopathy and myocarditis [6,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%